Evaluation of apical foramen distance in relation to the anatomical apex of mandibular molars by cone-beam computed tomography (CBCT) in a selected Iranian population - Armin Sadri; Ehsan Moudi; Soraya Khafri; Ali Soleymani (Babol University of Medical Sciences, 2019)
Introuduction: Knowledge of the internal anatomy and apical foramen of a tooth has always been a fundamental prerequisite for root canal therapy.Aim of the present study was to evaluate the distance of apical foramen in relation to the anatomical apex of mandibular molars by cone beam computed tomography (CBCT) in a selected Iranian population. Materials & Methods: In this cross- sectional study,97CBCT images of 25-50 years old patients were evaluated .the teeth were assessed in coronal plan. Results: Average (±SD) distance from apical foramen to the anatomical apex in the mesio-buccal and mesio-lingual, distal canal  were [0.938 (±0.294)mm], [0.964 (±0.315)mm] and [0.982 (±0.322)mm] respectively. no statistical difference was found  between right and left quadrant. Conclusion: This study demonstrated  that  1mm distance from radiographic apex in mandibular molars could be appropriate for root canal therapy.